Prevalence of thrombophilic gene polymorphisms in an Azari population of Iran - Nasrin Bargahi; Malak Farajzadeh; Ahmad Poursadegh-Zonouzi; Davoud Farajzadeh (Hematology Reports, 2014)
There is several evidence suggests that thrombophilic gene polymorphisms may influence susceptibility to thromboembolic events. The prevalence of these polymorphisms is different in various races and ethnics. Accordingly, we studied the prevalence of Factor V (G1691A and A4070G), prothrombin G20210A and PAI-1 4G/5G in healthy northwest population of Iran. In this prospective study, 500 healthy individuals, who had no history of both personal and family history of thromboembolic disorders, were selected as a sample of healthy population in northwestern Iran. Genotyping of these polymorphisms was performed using the amplification refractory mutation system-polymerase chain reaction method. No significant differences were detected between the expected and observed frequencies of FV G1691A and A4070G, prothrombin G20210A polymorphisms (P>0.05), while the expected frequency of 4G allele was significantly more than observed frequency in the studied population (P<0.01). These findings were compared with other reports from various populations. In conclusion, the allele frequency for FV G1691A and PAI-1 4G/5G polymorphisms showed relative consistency compared to those of previous studies, while the incidence pattern of FV A4070G polymorphism in Northwestern population of Iran showed conflicting results regarding other studied population. The prothrombin G20210A polymorphism was observed at a higher frequency than other studied populations.